La solidarietà come funzione sociale - Carlo Burelli; Francesco Camboni (Rivista di Estetica, 2023)
The article intends to tackle two key questions: what solidarity means and why it is considered a valuable trait for a society to exhibit. In so doing, it aims to bridge the literature gap between solidarity’s nature and its normative value. In this article, an original hypothesis is explored, i.e. that solidarity ought to be understood in functionalist terms, and that we should want it accordingly because solidarity discharges the crucial function of societal cohesion.